Analysis of the XRCC1 gene as a modifier of the cerebral response in ischemic stroke - Juo Suh-Hang H; Lin Hsiu-Fen; Dutra Ana VC; Mohrenweiser Harvey; Sen Souvik; Grewal Raji P (BMC, 2006)
Abstract Background Although there have been studies of the genetic risk factors in the development of stroke, there have been few investigations of role of genes in the cerebral response to ischemia. The brain responds to ischemia in a series of reactions that ultimately influence the volume of a stroke that, in general, correlates with disability. We hypothesize that polymorphisms in genes encoding proteins involved in these reactions could act as modifiers of this response and impact stroke volume. One of the pathways participating in the cerebral ischemic response involves reactive oxygen species which can cause oxidative damage to nucleic acids. DNA repair mechanisms are in place to protect against such damage and imply a role for DNA repair genes in the response of the brain to ischemia and are potential candidate genes for further investigation. Methods We studied two common polymorphisms in the DNA repair gene, XRCC1, C26304T and G28152A, in 134 well characterized patients with non lacunar ischemic strokes. We also performed a case control association study with 113 control patients to assess whether these variants represent risk factors in the development of ischemic stroke. Results Independent of etiology, the "T" allele of the C26304T polymorphism is significantly associated with larger stroke volumes (T-test analysis, p < 0.044; multivariate regression analysis, β = 0.23, p < 0.008). In the case control association study, we found that neither of these polymorphisms represented a risk factor for the development of stroke. Conclusion Our study suggests a major gene effect of the "T" allele of the C26304T polymorphism modulating the cerebral response to ischemia in non lacunar ischemic stroke.